Presence of pathogenic cryptococci on trees situated in two recreational areas in South Africa. (December 2017) - Vreulink, Jo-Marie; Khayhan, Kantarawee; Hagen, Ferry; Botes, Angela; Moller, Leandra; Boekhout, Teun; Vismer, Hester; Botha, Alfred
Abstract: Knowledge of the environmental prevalence of members of the Cryptococcus neoformans/Cryptococcus gattii species complex is important, since cryptococcal infection is acquired from the environment. We determined whether trees located in two South African recreational areas harboured pathogenic cryptococci and compared the isolates to clinical isolates obtained from Western Cape hospitals with molecular typing techniques. The majority of isolates originating from trees in a public park in Cape Town (PPCT) were C. gattii sensu stricto, followed by C. neoformans sensu stricto genotype AFLP1/VNI. The PPCT trees might be a source of infection, since all genotype AFLP1/VNI isolates from these trees and one clinical isolate belonged to the same sequence type (ST), i.e. ST23. Recombination and basidiospore production might be occurring in PPCT trees that contained C. gattii s.s. isolates belonging to both mating types. The presence of C. gattii s.s. in PPCT trees might therefore pose a risk to human health.